Targeting the mRNA endonuclease CPSF73 inhibits breast cancer cell migration, invasion, and self-renewal - Huiyun Liu; Daniel Heller-Trulli; Claire L. Moore (iScience, 2022)
Summary: Cleavage by the endonuclease CPSF73 and polyadenylation of nascent RNA is an essential step in co-transcriptional mRNA maturation. Recent work has surprisingly identified CPSF73 as a promising drug target for inhibiting the growth of specific cancers, triggering further studies on understanding CPSF73 regulation and functions in cells. Here, we report that a HECT-like E3 ligase, UBE3D, participates in stabilizing CPFS73 protein by preventing its ubiquitin-mediated degradation by the proteasome. Depletion of UBE3D leads to CPSF73 downregulation, a pre-mRNA cleavage defect, and dysregulated gene expression in cells. UBE3D dysfunction or chemical inactivation of CPSF73 inhibited migration and invasion as well as stem cell renewal phenotypes in vitro in triple-negative breast cancer cells. In addition, genetic overexpression of CPSF73 promoted breast cancer stemness and knocking down CPSF73 inhibited stem cell renewal properties. Together, our findings indicate that targeting the pre-mRNA processing nuclease CPSF73 has potential for breast cancer therapy.